Justifying abuse of women migrant domestic workers in Lebanon: the opinion of recruitment agencies - Ali Ghaddar; Sanaa Khandaqji; Jinane Ghattas (Elsevier, 2020)
Objective: Gender-based violence against women migrant domestic workers (WMDW) is a serious public health concern in the Middle East region. The current study is the first to explore abuse of WMDW as perceived by recruitment agency managers. Method: A qualitative study was conducted using 42 personal semi-structural interviews with agency managers in Lebanon. The interview guidelines were designed based on the standards set by the International Labor Organization (ILO) Convention No. 189. The information was transcribed in Arabic, and data was analyzed using thematic analysis. Results: The interviewees believe that WMDW are subject to abusive practices that represent various violations of the ILO Convention No. 189, including harassment and violence, compulsory labour, misinformation about conditions of employment, denial of periods of rest and restriction of movement and travel documents. In many situations, the interviewees justified some of these practices as being necessary to protect their business and to protect the workers. Conclusion: The results of this study have several policy implications for the protection of WMDW against abuse. Resumen: Objetivo: La violencia basada en el género contra las trabajadoras domésticas inmigrantes es un problema serio de salud pública en Medio Oriente. El presente estudio es el primero que explora el abuso de trabajadoras domésticas inmigrantes tal como lo perciben los/las gerentes de empresas de contratación de trabajo doméstico. Método: Se realizó un estudio cualitativo basado en 42 entrevistas personales semiestructuradas con gerentes de agencias en Líbano. El guion de la entrevista se basó en los estándares establecidos por el Convenio N.° 189 de la Organización Internacional del Trabajo (OIT). La información se transcribió en árabe y los datos se analizaron utilizando un análisis temático. Resultados: Las personas participantes creen que las trabajadoras domésticas inmigrantes están sujetas a prácticas abusivas que representan diversas violaciones del Convenio N.° 189 de la OIT, incluidos el acoso y la violencia, el trabajo forzado, la desinformación sobre las condiciones de trabajo, la negación de periodos de descanso, el encierro y el confinamiento del pasaporte. En muchas situaciones se justifican algunas de estas prácticas como necesarias para proteger sus negocios y proteger a las trabajadoras. Discusión: Los resultados de este estudio tienen varias implicaciones de política para la protección de las trabajadoras domésticas inmigrantes contra el abuso.